Propuesta de mejora en el proceso productivo de la empresa Calivan´S (2024)
The present project consists of developing a proposal to improve the production process of the company Calivan's, focusing on a type of mixed research, with descriptive, exploratory, applied, and descriptive approaches when carrying out the initial diagnosis of the situation current situation of the company,.